Investing in Not-for-Profit Sector Capacity: The Australian Capital Territory's Community Sector Development Program (CSDP) - Butcher, John (Blackwell Publishing, 2016)
In 2013 the Australian Capital Territory (ACT) government's Community Services Directorate (CSD) initiated a suite of projects designed to address the not-for-profit (NFP) community services sector's capacity to adapt to a rapidly changing policy and operational environment. In common with other Australian governments, the ACT relies upon NFP organisations to deliver a wide range of community-based human/social services. The procurement of services rendered to, or on behalf of, government by a third party provider under contract accounts for about 94% of the CSD's investment in the NFP community services sector. The ACT government, therefore, has a vested interest in ensuring that NFP providers are operationally capable, financially viable, and economically sustainable. Accordingly, the government launched a Community Sector Reform Program (CSRP) focussing on red tape reduction, sector development, and the establishment of a community sector outcomes framework. What lessons might the CSRP offer for other jurisdictions? This article describes a set of policy initiatives of the ACT government aimed at building not-for-profit sector capacity. It argues the need for comparative studies of similar initiatives across Australian jurisdictions. Australian Journal of Public Administration